2011
DOI: 10.1371/journal.pone.0019781
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Motif of a Bacterial Antigen Mediates Immune Responses via TLR2 Signaling

Abstract: The cross-talk between the innate and the adaptive immune system is facilitated by the initial interaction of antigen with dendritic cells. As DCs express a large array of TLRs, evidence has accumulated that engagement of these molecules contributes to the activation of adaptive immunity. We have evaluated the immunostimulatory role of the highly-conserved outer membrane lipoprotein P6 from non-typeable Haemophilus influenzae (NTHI) to determine whether the presence of the lipid motif plays a critical role on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 46 publications
1
9
0
Order By: Relevance
“…Essentially all the lipids of mycoplasmas are located in the cell membrane 32 . As a part of lipoprotein, the mycoplasma lipid moiety was the main component recognized by the innate immune system through Toll-like receptors (TLR) 2 and 6 33 34 . So we further investigated whether continuous passage caused gene variation affected biosynthetic pathways of Mycoplasma lipids.…”
Section: Resultsmentioning
confidence: 99%
“…Essentially all the lipids of mycoplasmas are located in the cell membrane 32 . As a part of lipoprotein, the mycoplasma lipid moiety was the main component recognized by the innate immune system through Toll-like receptors (TLR) 2 and 6 33 34 . So we further investigated whether continuous passage caused gene variation affected biosynthetic pathways of Mycoplasma lipids.…”
Section: Resultsmentioning
confidence: 99%
“…Here, we evaluated a candidate vaccine antigen selected based on our previous work describing the immunogenic and protective potential of the lipoprotein P6 (26). Although anti-P6 responses were diminished in the cigarette smoke exposed mice, the vaccine was still protective, and conferred immunity similar to that of unimmunized mice never exposed to smoke.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously demonstrated that T cell responses to P6 are associated with relative protection against NTHI infection in adults with COPD (24). The immunogenic nature of this highly conserved lipoprotein makes P6 a promising vaccine candidate for NTHI (25,26). The expectation would be that vaccine-induced immunity would minimize NTHI-mediated lung damage during COPD exacerbations.…”
Section: Introductionmentioning
confidence: 99%
“…HA consists of D-glucuronate and D-N-acetylglucosamine in an alternating sequence [ 3 ], lacking additional binding sites in larger molecules. The LPS binding of TLR4 [ 40 ] and between TLR2 and its ligand lipoprotein [ 41 ] is based on their lipophilic binding sites, and the binding activates the signalling cascade. HA as a hydrophilic molecule should not be able to bind directly to any of these lipophilic receptors, at least not to the same binding sites as the named ligands.…”
Section: Discussionmentioning
confidence: 99%